Frictional contact mechanics of asymmetric soft textures - Bowen, Leah K.; Long, Rong; Rentschler, Mark E. (Tribology international, 2023)
Soft textures with asymmetric friction properties in shear against soft substrates have significant promise for many applications, particularly in the medical field. Here, we fabricate textures with directional friction properties and investigate the interaction between soft textures and soft substrates in shear. We experimentally determine that shear direction, texture stiffness, and presence of a lubricant affect coefficient of friction. Finite element models support experimental results and suggest underlying mechanisms. For soft, directional textures sheared against soft untextured substrates, unlubricated friction is primarily governed by adhesion and contact area while lubricated friction is primarily governed by a plowing effect of texture into the substrate. [Display omitted] •Soft textures with asymmetric friction against soft substrates have many potential applications, particularly in medicine.•A simple manufacturing method produces soft textures with asymmetric friction against a soft substrate.•Asymmetric friction differs with texture stiffness and lubrication.•Unlubricated friction depends on contact area, while lubricated friction depends on substrate indentation and deformation.